Pengaruh Jarak Tanam dan Pemberian Auksin Terhadap PERTUMBUHAN Nanas (Ananas Comosus (L) Merr) di Antara Tanaman Sawit Di Lahan Gambut - Saputra, Wikastian Ade; Khoiri, Amrul; ', Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
ABSTRACT The number of plants per hectare is an important factor to get high yields. The number of plants widely unity depends on variety, age, soil fertility and water conditions. Through proper spacing between plant pineapple level of competition can be reduced as low as possible. The use of plant growth regulators (PGR) is required to support the growth and development of the pineapple plant. The aim of this study to determine the effect of spacing and administration of the growth hormone auxin on pineapple among immature oil palm plantations on peat land. This study was conducted with randomized block design experiment with 2 factors and 3 replications. The first factor is the spacing treatment, and for the second factor is the use of the hormone auxin. Then proceed to test the value of the middle HDS (Honestly Significant Difference) the 5% level. The parameters measured were plant height increase, in the number of leaves, the length of the leaves, leaf width accretion, plant fresh weight, dry weight of plants. The results showed the interaction of treatment and the spacing of the hormone auxin significant effect on the number of leaves but not on other parameters. Spacing factors did not significantly affect on all parameters. However, the hormone auxin treatment only significantly affects the leaf number, fresh and dry weight.. Keywords: Ananas comosus (L) Merr, Distance Planting, hormone auxin